Regulatory and legal principles for consolidatigh administrative and legal limitations on human rights and freedoms in ensuring road traffic safety by National police of Ukraine - Sobol, Yevhen; Palii, Valerii (Actual problems of law (Aktual’ni problemi pravoznavstva), 2024)
The article is devoted to one of the currently relevant problems of researching the regulatory and legal bases of establishing administrative and legal restrictions on human rights and freedoms in ensuring road traffic safety by the National Police of Ukraine. It has been updated that the issue of legislative consolidation of administrative and legal restrictions in ensuring road traffic safety by the bodies of the National Police of Ukraine, as one of the institutions of the integral system of public administration, is objectively mandatory to be covered in the scientific field and needs improvement in practice, i.e. in legislative acts. It is indicated that the legal peculiarity of the legal norms regarding administrative-legal restrictions in ensuring road traffic safety by the National Police of Ukraine consists, first of all, in the special subject of their regulation, which is social relations formed in the process of applying measures of administrative-legal restrictions on rights and human freedoms while ensuring road traffic safety by the National Police of Ukraine. It was determined that under the normative-legal basis of establishing administrative-legal restrictions on human rights and freedoms in ensuring road traffic safety by the National Police of Ukraine should be understood the totality of current normative-legal acts that define the concepts, principles and directions of administrative-legal restrictions, their forms and types, general rules and principles of implementation of administrative-legal restrictions, standards of their implementation, and also outline the legal status of the National Police bodies during the application of administrative-legal restrictions on human rights and freedoms while ensuring road safety. It has been established that the principles of providing administrative and legal restrictions, which are applied by the National Police bodies when ensuring road traffic safety in Ukraine, are contained in the following basic legal acts: 1) International acts; 2) Constitution of Ukraine; 3) Legislative acts (codes, laws); 4) Decrees of the President of Ukraine; 5) resolutions of the Cabinet of Ministers of Ukraine; 6) Acts of the Ministry of Internal Affairs and the National Police of Ukraine.